Benefits of Parasitism in Polluted Environments: A Review and Perspectives - Goutte, Aurelie; Molbert, Noëlie (Frontiers in Ecology and Evolution, 2022)
The frequency and strength of biotic interactions are thought to be shaped by environmental conditions. Here, we review and discuss the potential effects of toxic chemicals in driving shifts along the parasite-mutualist continuum. Some parasites have the astonishing capacity to accumulate trace metals, but also organic pollutants, from various taxa within freshwater, marine and terrestrial ecosystems. Recent studies have provided evidence of clear benefits for the host: when exposed to contaminants, infected organisms exhibited reduced contamination levels, less severe oxidative stress and histological alterations, as well as higher body condition and survival rate compared to their uninfected conspecifics. Such effects might arise when the costs of parasitism are lower than the benefits in specific environmental conditions. Assessing the potential outcomes for parasites exploiting contaminated hosts is a crucial but neglected issue, since ecotoxicological effects on parasites may alter interspecific relationships. We identify possible avenues for future research, using innovative tools and long-term experimental manipulations of both parasitism and pollution, to better understand how toxic chemicals can modulate the strength and direction of host-parasite interactions.